Stature estimation from length of fingers in South Indian population – A cross sectional study - Pournima; James Rajesh, J; Roop Kumar, K M; Siva Reddy, B; Jothi Marie Feula, A (Journal of Indian Academy of Forensic Medicine, 2019)
For years, anthropologists and medico legal experts are using stature as a main feature of personal identification and till now stature has got a great significance. This paper is a study conducted in the department of Forensic Medicine and Toxicology in Sri Venkateshwaraa Medical College Hospital and Research Centre, Ariyur, Puducherry, among the Under Graduate students. A stadiometer was used to measure height on standing erect in anatomical position with bare foot against a wall. The head was kept in the eye-ear-eye plane and then the height was measured to the nearest 0.1 cm. Asliding calliper was used to measure the finger length. All the measurements were taken at a specific time to avoid the diurnal variation. The results were analysed and a regression equation was derived for each of the finger. Out of ten fingers, eight proved to be statistically significant. The study results will augment the existing data and will be a tool of relevance to anthropologists and medico legal experts.